On the convexity of the Goldenblat-Kopnov yield condition (Archives of Mechanics - Test, 1997)
The present paper is aimed at the formulation of sufficient conditions of convexity for the Goldenblat-Kopnov yield condition. The essence of the proposed approach consists in the transposition of convexity of hypersurface from the six-dimensional stress space to the three-dimensional space of the principal stresses, and in the presentation of a surface in the Haigh-Westergaard stress space.